Developing Concept Construction Based Abstract Algebra Textbook to Improve Students’ Understanding - Zuhrotun Nazihah; Dwi Nurcahyo (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
The purpose of this study is to develop and produce a concept construction based abstract algebra textbook to improve students’ understanding. The development method used in this study was 3D method, they are define, design and develop. It refered to Tiagrajan’s 4D method. Based on the data analysis results, the level of textbook’s validity produced was achieving valid criteria without revision, but the results of students’ learning tests showed 92,7% students reached the criteria of understanding objects so the textbook could be said effective. Therefore, based on the results, it could be concluded that the textbook could improve students’ understanding and it was suitable to be used as abstract algebra’s learning book in the learning process.